Cooperation among tectonic and surface processes in the St. Elias Range, Earth's highest coastal mountains. Issue 14 (30th July 2015) - Enkelmann, Eva; Koons, Peter O.; Pavlis, Terry L.; Hallet, Bernard; Barker, Adam; Elliott, Julie; Garver, John I.; Gulick, Sean P. S.; Headley, Rachel M.; Pavlis, Gary L.; Ridgway, Kenneth D.; Ruppert, Natalia; et al.
Abstract: Investigations of tectonic and surface processes have shown a clear relationship between climate‐influenced erosion and long‐term exhumation of rocks. Numerical models suggest that most orogens are in a transient state, but observational evidence of a spatial shift in mountain building processes due to tectonic‐climate interaction is missing. New thermochronology data synthesized with geophysical and surface process data elucidate the evolving interplay of erosion and tectonics of the colliding Yakutat microplate with North America. Focused deformation and rock exhumation occurred in the apex of the colliding plate corner from > 4 to 2 Ma and shifted southward after the 2.6 Ma climate change. The present exhumation maximum coincides with the largest modern shortening rates, highest concentration of seismicity, and the greatest erosive potential. We infer that the high sedimentation caused rheological modification and the emergence of the southern St. Elias, intercepting orographic precipitation and shifting focused erosion and exhumation to the south. Key Points: Geophysical and geologic data reveal the transient state of the St. Elias orogen Rheologic modification of the Yakutat plate changes orogenic deformation rates and location Plio‐Pleistocene climate shift drives the orogen into transient state with 1–2 Myr response times